Kriminalitas di Kalimantan Timur Tahun 1929 Berdasarkan Koran Bintang Borneo Author(s)Resty Apriliani - Apriliani, Resty; Azmi, Muhammad; Kusumawijaya, Rizal Izmi (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
Crime is an act that is detrimental and disrupts people’s comfort and life. Crime has occurred a long time ago, even when Indonesia was still called the archipelago in 1929. The research aims to find out how crime developed in East Kalimantan in 1929. This research uses the historical research method according to Kuntowijoyo which consists of five stages. The first stage is selecting a topic. The second source collection consists of two sources. Primary sources in this research use the Bintang Borneo Newspaper published in 1929. Secondary sources in this research use several history and crime journals. The third stage is Verification. Fourth stage Interpretation. Fifth Stage of Historiography. The results of this research are that when the world experienced the Great Depression in 1929, the majority of crimes that occurred in East Kalimantan in January 1929 were cases of robbery. Other crimes include murder, fights and fraud committed by the police.